Topical Issues of Religious Educational Work of Orthodox Spiritual Mission in Altai In Early 1900s - Aleksandrovich Kreydun, Yury; Ivanovna Nekhvyadovich, Larisa (Opción, 2019)
The paper refers to archive sources to reconstruct the record of the Altai Spiritual Mission and explores the social and political factors that hindered the organiza- tion’s missionary causes in Altai in the early 1900ies. Ideals and beliefs at the core of Burkanism and the aspects of their establishment across Gorny Altai are out- lined. Problems of material procurement of the Altai Mission are addressed based on the analysis of income structure. A breakdown of the 1910-1911 spending cal- culation points at a considerable positive budget trend of the Altai Mission. The paper identifies the role of the Orthodox Missionary Society and philanthropists in providing funding for the mission and draws a conclusion that in absence of direct state support for religious education of the native peoples of Siberia the possibility emerged for the formation of non-state religious educational structures.